2017
DOI: 10.1016/j.clinmicnews.2017.08.001
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Molecular Panels: What Is in the Best Interest of the Patient? A Review of Patient Outcome Studies for Multiplex Panels Used in Bloodstream, Respiratory, and Neurological Infections

Abstract: In the clinical microbiology laboratory, the focus when choosing new tests is often on performance, turnaround time, and labor needs. This review examines available rapid, multiplexed tests from a different perspective: that of the patient. It considers whether published evidence supports the notion that use of rapid, on-demand tests (as opposed to batched testing) leads to better patient outcomes and whether broad, syndrome-based, multiplexed panels translate into better patient care than narrower monoplex or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 32 publications
0
3
0
1
Order By: Relevance
“…Tras la intervención, se reportan terapias dirigidas rápidas, sin esperar el resultado del antibiograma, por lo que las pruebas rápidas de diagnóstico, ayudaron a tomar las decisiones basada en la bacteria identificada 8,10,11 . Además se reporta una menor utilización de antibióticos empíricos inapropiados 3,[12][13][14] , especialmente en el grupo de bacterias Gram positivas 15 , consideramos que lo anterior puede corresponder a que los genes de resistencia para bacterias gram positivas testeados por la prueba, como el mecA y van A/B, ayudan al médico a la toma de decisiones para desescalar o suspender antibióticos, lo que no sucede con bacterias gram negativas, puesto que en hospitales con índices de resistencia bajos para blaKPC, la información suministrada sobre la resistencia de carbapenemasas es de menor utilidad que la tipificación de beta lactamasas de espectro extendido (ESBLs/BLEEs). Por lo tanto, la decisión de desescalar carbapenémicos queda sometida al análisis de factores de riesgo de pacientes que puedan tener este tipo de resistencia 16 , especialmente para bacterias como Klebsiella spp., Pseudomonas spp.…”
Section: Discussionunclassified
“…Tras la intervención, se reportan terapias dirigidas rápidas, sin esperar el resultado del antibiograma, por lo que las pruebas rápidas de diagnóstico, ayudaron a tomar las decisiones basada en la bacteria identificada 8,10,11 . Además se reporta una menor utilización de antibióticos empíricos inapropiados 3,[12][13][14] , especialmente en el grupo de bacterias Gram positivas 15 , consideramos que lo anterior puede corresponder a que los genes de resistencia para bacterias gram positivas testeados por la prueba, como el mecA y van A/B, ayudan al médico a la toma de decisiones para desescalar o suspender antibióticos, lo que no sucede con bacterias gram negativas, puesto que en hospitales con índices de resistencia bajos para blaKPC, la información suministrada sobre la resistencia de carbapenemasas es de menor utilidad que la tipificación de beta lactamasas de espectro extendido (ESBLs/BLEEs). Por lo tanto, la decisión de desescalar carbapenémicos queda sometida al análisis de factores de riesgo de pacientes que puedan tener este tipo de resistencia 16 , especialmente para bacterias como Klebsiella spp., Pseudomonas spp.…”
Section: Discussionunclassified
“…They indicated that this assay had a sensitivity of 98.9-100% and specificity of 80% (Altun et al, 2013). The recent FDA-approved Accelerate Pheno assay (Accelerate Diagnostics, Tucson, AZ) employs time-lapse microscopy coupled with image analysis for susceptibility assays to pre-define panels of drugs on blood cultures of several Gram-negative (E. coli, Klebsiella species, Enterobacter species, Proteus species, Citrobacter species, S. marcescens, Pseudomonas aeruginosa, A. baumannii), Gram-positive (S. aureus, Staphylococcus lugdunensis, CoNS species, E. faecalis, E. faecium, Streptococcus species), and yeast (Candida albicans, Candida glabrata) isolates in 6 hours (Sullivan, 2017).…”
Section: Molecular Methods For Pathogen Identification In Positive Blmentioning
confidence: 99%
“…Since its appearance on the market, scientific evidence has been generated about its impact on the different process and outcome indicators [17,18]. The former include time to optimisation of antibiotic treatment and duration of antibiotic therapy.…”
Section: What Is the Available Evidence On The Impact Of Using These ...mentioning
confidence: 99%